2010
DOI: 10.1117/12.846731
|View full text |Cite
|
Sign up to set email alerts
|

3D-AFM tip to tip variations and impact on measurement performances

Abstract: The CD metrology requirements for advanced node developments and process control are becoming more and more restrictive with shrinkage of dimensions. Currently in R&D, and more particularly in the process development in lithography or etching step, we have to cope with sub40nm trenches CD measurements for sub-28nm nodes development.For such requirements, we are using the 3D-AFM technology as a complementary technique to CD-SEM. Indeed, as CD-SEM is limited in giving accurate information about profiles, the 3D-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…For example, Foucher, et al first reported observations indicating that the lateral stiffness of a tip could affect the consistency of the tip calibration using a type of sample known as a vertical parallel structure (VPS). [8] This was a surprising observation since it seems to indicate a breakdown in the assumption that for given instrument parameters there is fixed offset between the geometrical tip width and the effective tip width. In practical application terms, their results indicated the presence of a non-geometrical tip contribution that did not completely cancel when performing a tip calibration and subsequent measurement.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Foucher, et al first reported observations indicating that the lateral stiffness of a tip could affect the consistency of the tip calibration using a type of sample known as a vertical parallel structure (VPS). [8] This was a surprising observation since it seems to indicate a breakdown in the assumption that for given instrument parameters there is fixed offset between the geometrical tip width and the effective tip width. In practical application terms, their results indicated the presence of a non-geometrical tip contribution that did not completely cancel when performing a tip calibration and subsequent measurement.…”
Section: Introductionmentioning
confidence: 99%